PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP NEGERI 31 MEDAN - Elisabet Bani Putri Nduru; Israil Sitepu; Frida Marta Simorangkir (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this study was to determine the effect of the Team Assisted Individualization (TAI) type cooperative learning model on students' mathematical problem solving skills in learning mathematics at SMP Negeri 31 Medan. The research method used in this research is quasi-experimental method or pseudo-experiment, and the type of data used is quantitative data. This research uses Pretest-Posttest Control Group research design. The research instrument used is a problem solving ability test, while the data processing technique used in this study is a two-party t test hypothesis test with a significance value of 0.05 and the sample is taken randomly with a total of 62 students. The Lcount value of the experimental class posttest is 0.103 while the Ltabel value is 0.159 with a significance level of 0.05, so it can be concluded that Lcount < Ltabel (0.103 < 0.159) then both classes are normally distributed (HO rejected). The experimental class posttest Fcount value is 0.748 while the Ftabel value is 0.543, with a significance level of 0.05, so it can be concluded that Fcount> Ftabel (0.748> 0.543) then HO is rejected which means the sample comes from a homogeneous data group. Based on the two-party t test statistical test with dk = n1 + n2 - 2 with a significance level of 0.05, it can be concluded that there is an effect of the Team Assisted Individualization (TAI) type cooperative learning model on students' mathematical problem solving skills.